Improving perceptions of value to teaching and research staff: The next challenge for academic libraries. (September 2014) - Creaser, Claire; Spezi, Valérie
This article investigates the value, and perceptions of value, of academic libraries to teaching and research staff by examining working relationships between libraries and academic departments in universities. Eight case studies were undertaken in the US, the UK and Scandinavia. Primary findings were analysed and triangulated with a series of short surveys to ascertain whether they resonated with other librarians' experiences. The article offers examples of good practice in the area of partnership building for academic libraries to improve their value to, or perceptions of value by, teaching and research staff, as well as raise their profile and better market their services to this category of users. Those examples may be of interest to fellow library practitioners and researchers interested in exploring further library-faculty interaction and collaboration.